Neoadjuvant osimertinib and chemotherapy for stage IIIA primary pulmonary carcinosarcoma with EGFR 19DEL mutation: A case report - Wang, Hongming; Wu, Zhijun; Du, Yangfeng; Wu, Tao; Tian, Wei; Dong, Wen; Cai, Juan; Zheng, Jiang; Zhang, Yan; Li, Shiyan; Xu, Wei; Qin, Jing; et al. (Frontiers in Oncology, 2023)
Epidermal growth factor receptor (EGFR) mutations have been frequently detected in patients with pulmonary adenocarcinoma. EGFR Exon 19Del and 21L858R mutations are the two most common EGFR mutations. EGFR-tyrosine kinase inhibitors (TKIs) are widely employed to treat patients with non-small cell lung cancer (NSCLC) harboring EGFR mutations. Recently, there has been rapid growth in clinical trials assessing neoadjuvant targeted therapy, indicating good application prospects owing to high efficiency and low toxicity. Herein, we discuss the case of a 56-year-old male patient who was initially diagnosed with stage IIIA pulmonary adenocarcinoma (AJCC,8th edition) of the left lower lung with an EGFR Exon 19Del mutation. The patient was treated with osimertinib but failed to undergo timely review and surgery. Subsequently, the patient underwent two cycles of neoadjuvant chemotherapy (NAC) combined with neoadjuvant targeted therapy. After the tumor load and size had significantly decreased, radical surgery was successfully performed under thoracoscopy. However, postoperative pathology revealed carcinosarcoma, pT2aN0M0, stage IB, and the pathological response was 50%. The present case report provides practical clinical evidence for the application of neoadjuvant targeted therapy combined with chemotherapy for locally advanced primary pulmonary carcinosarcoma with EGFR mutation.